Impact of snow on underground smoldering wildfire in Arctic-boreal peatlands - Qin, Y; Zhang, Y; Chen, Y; Lin, S; Shu, Y; Huang, Y; Huang, X; Zhou, M (Environmental Science & Technology, 2025)
202502 bcch Version of Record RGC Early release ACS (2025) TA